2004
DOI: 10.1128/aac.48.12.4650-4653.2004
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Telithromycin in Plasma and Soft Tissues after Single-Dose Administration to Healthy Volunteers

Abstract: By use of microdialysis we assessed the concentrations of telithromycin in muscle and adipose tissue to test its ability to penetrate soft tissues. The ratios of the area under the concentration-versus-time curve from 0 to 24 h to the MIC indicated that free concentrations of telithromycin in tissue and plasma might be effective against Streptococcus pyogenes but not against staphylococci and human and animal bite pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…However, all these parameters cannot explain the discrepancy between the results of the single-dose part and the multiple-dose part of the present study because no significant change in pK a , the pH of the tissue, or the octanol/water partition coefficient is expected to occur between single and multiple doses in our healthy study population. Thus, our observation is not yet fully understood, but it should be mentioned that similar behaviors were found by our group for gemifloxacin (9) and telithromycin (7). This underlines the need for novel strategies for the investigation of the tissue pharmacokinetics of antibiotics.…”
Section: Discussionmentioning
confidence: 80%
“…However, all these parameters cannot explain the discrepancy between the results of the single-dose part and the multiple-dose part of the present study because no significant change in pK a , the pH of the tissue, or the octanol/water partition coefficient is expected to occur between single and multiple doses in our healthy study population. Thus, our observation is not yet fully understood, but it should be mentioned that similar behaviors were found by our group for gemifloxacin (9) and telithromycin (7). This underlines the need for novel strategies for the investigation of the tissue pharmacokinetics of antibiotics.…”
Section: Discussionmentioning
confidence: 80%
“…Like tigecycline, telithromycin displays extensive tissue distribution, with a volume of distribution of 2.9 L/kg [87,89], suggesting that concentrations may be higher at the site of action. This is also supported by a microdialysis study in healthy volunteers with telithromycin that found AUC 0-8 ratios of free tissue/free plasma of 2.1 ± 1.6 and 1.5 ± 0.9 for subcutaneous adipose and muscle tissue, respectively [90]. Another explanation for a low PK/PD targeted index is that these antibiotics accumulate intracellularly, especially azithromycin and telithromycin [91][92][93].…”
Section: Macrolides Ketolides and Azalidesmentioning
confidence: 91%
“…Telithromycin achieves high and prolonged concentrations in the lung (Kadota et al 2002 ;Khair et al 2001 ), nasal mucosa and ethmoid bone (Kuehnel et al 2005 ), tonsils (Gehanno et al 2003 ), female genital tract (Mikamo et al 2003 ), and infl amed blister fl uid (Namour et al 2002 ). Its free concentration in soft tissues (subcutis and muscle) is close to the free serum concentration (Gattringer et al 2004 ;Traunmuller et al 2009 ).…”
Section: Distributionmentioning
confidence: 94%